THE 2020 AMENDMENTS TO THE CONSTITUTION OF THE RUSSIAN FEDERATION AND THE IDEOLOGY OF A SOVEREIGN DEMOCRATIC AND WELFARE STATE - Vasilievich Ivanov, Ivan (Revista Gênero e Interdisciplinaridade, 2020)
The article examines the constitutional and legal content of the 2020 amendments to the Constitution of the Russian Federation. The study aims to substantiate the existence of a coincidence of public opinion and public demand in Russia with the amendments to the Constitution of the Russian Federation, as well as to analyze the impact of these amendments on changing the citizens’ constitutional rights. The results of the study are the assessment of the impact of amendments to the Constitution of the Russian Federation on a possible change in socio-political life in Russia, strengthening guarantees, and increasing the scope of citizens’ social rights. The article defines the peculiarity of the constitutional system of Russia, which was the result of the formation of a new political and public life after 1991, and reflects liberal political and legal values, stating that the citizens’ social rights and the ideas of state sovereignty were largely beyond them. A change in the current situation is possible through the harmonization and succession of Russia and the Soviet state, with the adoption of the social values of the USSR in modern Russia. The conclusions of the article boil down to a positive assessment of the amendments to the Constitution of the Russian Federation, which, according to the author, will lead to the formation of the ideology of a real sovereign democratic and welfare state in Russia. Besides that, the author notes in the conclusions that the establishment of Russia as a democratic state, with the recognition of a market economy, separation of powers, and the rule of law, is impossible without guaranteeing the social rights of all Russian citizens.